Combination inhaler is effective in mild asthma. (28th March 2022) - Saul, Helen; Gursul, Deniz; Cassidy, Samantha; Hinks, Timothy
The study: Crossingham I, Turner S, Ramakrishnan S, et al. Combination fixed-dose β agonist and steroid inhaler as required for adults or children with mild asthma: a Cochrane systematic review. BMJ Evid Based Med 2021; doi:10.1136/bmjebm-2021-111764 . To read the full NIHR Alert, go to: https://evidence.nihr.ac.uk/alert/combination-inhaler-is-effective-in-mild-asthma/